2015
DOI: 10.1002/hbm.22951
|View full text |Cite
|
Sign up to set email alerts
|

Resting‐state functional connectivity and presynaptic monoamine signaling in Alcohol Dependence

Abstract: Alcohol Dependence (AD) is a chronic relapsing disorder with high degrees of morbidity and mortality. While multiple neurotransmitter systems are involved in the complex symptomatology of AD, monoamine dysregulation and subsequent neuroadaptations have been long postulated to play an important role. Presynaptic monoamine transporters, such as the vesicular monoamine transporter 1 (VMAT1), are likely critical as they represent a key common entry point for monoamine regulation and may represent a shared pathway … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 55 publications
1
23
0
Order By: Relevance
“…2b,c and Supplementary Table S2 ). In addition, we performed an EWAS on neuroimaging network activation as a function of alcohol use with peripheral blood from individuals with AUD that previously underwent resting state functional connectivity (RSFC) analysis 36 ( n = 68) ( Supplementary Table S3 ). Results of these 3 EWAS did yield various methylation sites that were associated with disease phenotypes ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2b,c and Supplementary Table S2 ). In addition, we performed an EWAS on neuroimaging network activation as a function of alcohol use with peripheral blood from individuals with AUD that previously underwent resting state functional connectivity (RSFC) analysis 36 ( n = 68) ( Supplementary Table S3 ). Results of these 3 EWAS did yield various methylation sites that were associated with disease phenotypes ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been found that the gain-of-function A-allele (136Ile) is protective against bipolar disorder ( Lohoff et al, 2006 ), and the AA (Ile/Ile) homozygotes have lower STAI state and trait scores ( Lohoff et al, 2008b ). Very recently, the A-allele (136Ile) has been found to be associated with reduced connectivity in networks that show a general increased connectivity in alcoholics, indicating a potential protective effect ( Zhu et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…These taskfree fMRI data can be used to extract resting state networks (RSNs), which consist of brain regions that are temporally -and presumably functionally --coupled (Greicius, 2008;Greicius et al, 2003;Lowe et al, 2000). There is now an emergent literature on alterations in FC within the AUD population, although most of the work has been done in abstinent individuals (Camchong et al, 2013;Chanraud et al, 2011;Jansen et al, 2015;Müller-Oehring et al, 2015;Sjoerds et al, 2017;Zhu et al, 2015). There are only a few studies that report findings in either at-risk drinkers (Vergara et al, 2017) or currently drinking alcoholdependent subjects (Weiland et al, 2014;Zhu et al, 2015), albeit with equivocal results.…”
Section: Introductionmentioning
confidence: 99%